The Tumor Microenvironment in SCC: Mechanisms and Therapeutic Opportunities - Amôr, Nádia Ghinelli; Santos, Paulo Sérgio da Silva; Campanelli, Ana Paula (Frontiers in Cell and Developmental Biology, 2021)
Squamous cell carcinoma (SCC) is the second most common skin cancer worldwide and, despite the relatively easy visualization of the tumor in the clinic, a sizeable number of SCC patients are diagnosed at advanced stages with local invasion and distant metastatic lesions. In the last decade, immunotherapy has emerged as the fourth pillar in cancer therapy via the targeting of immune checkpoint molecules such as programmed cell-death protein-1 (PD-1), programmed cell death ligand-1 (PD-L1), and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4). FDA-approved monoclonal antibodies directed against these immune targets have provide survival benefit in a growing list of cancer types. Currently, there are two immunotherapy drugs available for cutaneous SCC: cemiplimab-rwlc and pembrolizumab; both monoclonal antibodies (mAb) that block PD-1 thereby promoting T-cell activation and/or function. However, the success rate of these checkpoint inhibitors currently remains around 50%, which means that half of the patients with advanced SCC experience no benefit from this treatment. This review will highlight the mechanisms by which the immune checkpoint molecules regulate the tumor microenvironment (TME), as well as the ongoing clinical trials that are employing single or combinatory therapeutic approaches for SCC immunotherapy. We also discuss the regulation of additional pathways that might promote superior therapeutic efficacy, and consequently provide increased survival for those patients that do not benefit from the current checkpoint inhibitor therapies.